STEAM Learning Training Based on Robot for Mission (R4M) Coding to Support 21st Century Thinking Skills - Carolina Sri Athena Barus; Ashari Bayu Prasada Dulhasyim; Vederico Pitsalitz Sabandar; Freddy Oakley Palapessy; Idham (Unram Journal of Community Service, 2026)
The Community Empowerment Partnership Program (PKM) implemented at SMA Negeri 1 Ambon aims to support the improvement of 21st century skills through Science, Technology, Engineering, Art, and Mathematics (STEAM) learning training based on Coding Robot For Mission (R4M). This program was initiated in response to the challenges of digital era education, which demands critical thinking, problem solving, collaboration, and communication skills, both to prepare students for the global workforce and to promote the advancement of the Maluku region. The implementation of activities was based on the results of an analysis of the situation and the needs of partners, which were then agreed upon jointly. The method used is Community Development, which is an empowerment and partnership-based approach, actively involving the school community in every stage of the activity, from socialization, module development, coding, and robotics design training, to technology implementation assistance. The results of this program show that SMA Negeri 1 Ambon, as a partner, has great potential as a pioneer in the application of STEAM-based learning and digital literacy, but still faces significant limitations. Nevertheless, teachers and school officials show high enthusiasm and readiness for change. With the support of training, mentoring, and the provision of facilities, SMA Negeri 1 Ambon has the potential to become a model for the implementation of STEAM and coding in Maluku Province, while also strengthening students' 21st-century skills in a sustainable manner.